Social issues in sport - Woods, Ron, 1943 Nov. 6- (Human Kinetics, 2011)
Offers an introduction to the roles of sport and physical activity in society and the perfect tool for examining sport from a critical perspective. This title provides a look at the issues, contradictions and confusion surrounding sport for students in sport management, sport sociology, or other areas of sport studies.